The effect of headgroup methylation on polymorphic phase behaviour in hydrated N-methylated phosphoethanolamine: palmitic acid membranes - Allen,ME; Elani,Y; Brooks,NJ; Seddon,J (Soft Matter, 2021)
Mixtures of fatty acids and phospholipids can form hexagonal (HII) and inverse bicontinuous cubic phases, the latter of which are implicated in various cellular processes and have wide-ranging biotechnological applications in protein crystallisation and drug delivery systems. Therefore, it is vitally important to understand the formation conditions of inverse bicontinuous cubic phases and how their properties can be tuned. We have used differential scanning calorimetry and synchrotron-based small angle and wide angle X-ray scattering (SAXS/WAXS) to investigate the polymorphic phase behaviour of palmitic acid/ partially-methylated phospholipid mixtures, and how headgroup methylation impacts on inverse bicontinuous cubic phase formation. We find that upon partial methylation of the phospholipid headgroup (1 or 2 methyl substituents) inverse bicontinuous cubic phases are formed (of the Im3m spacegroup), which is not the case with 0 or 3 methyl substituents. This shows how important headgroup methylation is for controlling phase behaviour and how a change in headgroup methylation can be used to controllably tune various inverse bicontinuous phase features such as their lattice parameter and the temperature range of their stability.